Going Dutch in Environmental Policy - Tuininga, Eric-Jan (Ökologisches Wirtschaften - Fachzeitschrift, 1995)
In many discussions on Environmental Policy the Dutch efforts since 1989 are mentioned as a laud-able example for other governments. But after five years of hard work and three National Environ-mental Policy Plans (nepp), the effectiveness of all these policy plans are still up for debate, most of all in the Netherlands itself. Environmental policy is more than writing plans and as it turns out the implementation of policies is more unruly than expected. OECD's recent 'Environmental Performance Review' of the Dutch policies even wondered if the Dutch planning and agreement approach could backfire and prevent some real solutions.
Keywords: Dutch Environmental Policy